2001
DOI: 10.1016/s0924-9338(01)00577-6
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical arrangement of psychiatric symptoms in the context of schizophrenia

Abstract: Foulds' model proposing a four-class hierarchical structure of mental illness represents an interesting dimension of psychiatric research and discussion and probably has a significant potential on diagnosis, taxonomy, therapeutics and theory. Psychiatric symptoms were investigated in a group of 244 schizophrenic patients with the purpose of analyzing Foulds and Bedford's notion that psychiatric symptoms are arranged hierarchically. To achieve this the R (recent) version of the Delusions, Symptoms, States, Inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…This was in keeping with the notion that the hierarchical model is applicable only to acute patients [13,26]. Hence, no other study has included a large number of outpatients with chronic schizophrenia, not to mention non-patients – apart from that by the original authors of the DSSI [10]. The results of our study however suggested that the DSSI can be applied as effectively to both subclinical stabilized chronic illness group and non-patients as a screening measure for presence of active symptoms.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This was in keeping with the notion that the hierarchical model is applicable only to acute patients [13,26]. Hence, no other study has included a large number of outpatients with chronic schizophrenia, not to mention non-patients – apart from that by the original authors of the DSSI [10]. The results of our study however suggested that the DSSI can be applied as effectively to both subclinical stabilized chronic illness group and non-patients as a screening measure for presence of active symptoms.…”
Section: Discussionmentioning
confidence: 85%
“…Accordingly, a self-report measure developed to assess the degree of adverse change in personal functioning and severity of clinical disorder in a hierarchical arrangement has been proposed previously by Foulds and Bedford [9]. The central notion is that starting with those without significant level of illness, or not personally ill (NPI), patients could be categorized according to a four-class hierarchical model of the severity of mental illness as follows: dysthymic states (DS) consisting of manifestations of states of anxiety, depression, and/or elation; neurotic symptoms (NS) involving conversion, dissociation, phobia, compulsion, and rumination; integrated delusion (ID) with delusions of persecution, grandeur, and/or contrition; and delusions of disintegration (DD) representing a single syndromal group corresponding to schizophrenia with considerable extent of personal disintegration as an agent of his/her own feelings, thoughts and actions [10,11]. The central hypothesis of this model is inclusive, non-reflexive relationship among the classes, which simply posits that the membership in the higher class also entails membership in the lower ones and that the converse does not hold.…”
Section: Introductionmentioning
confidence: 99%
“…To assess anxiety, we examined responses to seven anxiety-related items included within the Delusions-Symptoms-State Inventory (DSSI) anxiety scale. This scale has also been widely used in clinical (Angelopoulos and Economou, 2001;Bedford and Presly, 1978) and community samples (Rodgers et al, 2000). For the purposes of this study, the presence of significant anxiety was defined as endorsing at least four anxiety items.…”
Section: Assessments Of Depressive and Anxiety Symptomsmentioning
confidence: 99%